Analysis of aBiomass-fueled Fish Dryer with a Microcontroller Based Blower System - Iskandar; Banta Cut; Bambang Nurcipto; Rahmad Bahri (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
This study analyzes the performance of a biomass-fueled fish dryer equipped with a blower and an automatic control system based on an Arduino Mega 2560 microcontroller. The system consists of a combustion chamber, a drum-shaped drying chamber, a blower, a type-K temperature sensor, and a MAX6675 module controlled via a solid-state relay (SSR). Tests were conducted under no-load and load conditions using milkfish. The results showed average drying temperatures of 78.76 °C and 64.1 °C, with drying rates of 74.2 g/h and 70.6 g/h, respectively. The final moisture contents were 19.1% and 19.4%. The temperature control system operated stably without overshoot and effectively regulated the blower. Heat transfer efficiency reached 64.48% and increased to 70.26%, while the overall thermal efficiency was 3.12% due to the open system design without insulation. Coconut shell biomass proved to be an economical and more sustainable energy source.